KERAJAAN INDRAGIRI PADA MASA PEMERINTAHAN PADUKA MAULANA SRI SULTAN ALAUDDIN ISKANDAR SYAH JOHAN ZIRULLAH FIL ALAM (NARASINGA II) TAHUN 1473-1532 - Hari Sulistiawati; Isjoni '; Kamaruddin ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: Indragiri Kingdom is a Malay Kingdom that stood around the end of the XII century, this kingdom is located on the banks of the same named river. With the first King of Merlang I, Narasinga I, Merlang II and arrived at Narasinga II who held Paduka Maulana Sri Sultan Alauddin Iskandar Syah Johan. Who ruled from 1473-1508 were in Malacca, 1508-1532 were in Indragiri. The purpose of this study are (1) To know the beginning of the founding of Indragiri Kingdom (2) To find out the process of picking King Narasinga II from Melaka to Indragiri (3) To find out what reason King Narasinga II moved the royal center (4) To know how the history of King Narasinga II's resistance (5) Know the end of the reign of King Narasinga II. This study uses historical method. The result of this research is Originally Indragiri Kingdom called Keritang Kingdom whose kingdom is located in Keritang Village Indragiri Regency. Called Indragiri because Narasinga II began to return to Indragiri picked by Datuk Patih using Raft Kulim and move the royal center from Keritang to Pekantua. Then moved again to the Old Town Village to avoid attacks from the Portuguese. Narasinga II married Dang Purnama and blessed with 2 children one of whom became the successor to the throne of Indragiri Kingdom.Keywords: History, Government, Narasinga II, Indragiri